Evaluating the role of astragalus polysaccharide in modulating immune infiltration and enhancing prognostic biomarkers in pediatric acute myeloid leukemia - He, Min-Hui; Zhang, Xian-Hui; Zhang, Ji-Hong; Pan, Jie; Yang, Chao (Frontiers in Pharmacology, 2025)
BackgroundChildhood acute myeloid leukemia (AML) constitutes a significant proportion of pediatric malignancies, with current treatment options remaining limited. This study aimed to investigate the role of Astragalus polysaccharide (APS) in immune infiltration and prognosis of pediatric AML.MethodsDifferentially expressed genes (DEGs) were identified from the GEO database (dataset GSE2191), and APS-related genes (APSRGs) were obtained from the Swiss Target Prediction platform. DEGs with |logFC| > 1 and p < 0.05 were intersected with APSRGs to identify APS-related differentially expressed genes (APSRDEGs), visualized using a Venn diagram. A protein-protein interaction (PPI) network analysis was conducted to identify hub genes. Gene Ontology (GO) and KEGG enrichment analyses were performed to determine biological processes (BP), cellular components (CC), molecular functions (MF), and relevant pathways associated with the hub genes. Correlation analysis, receiver operating characteristic (ROC) curve analysis, and immune infiltration analysis were conducted to assess the relationship between hub genes and pediatric AML.ResultsThe GSE2191 dataset was divided into pediatric AML (PAML) and control groups. A total of 1,881 DEGs were identified, of which 20 were APSRDEGs. PPI network analysis revealed that 13 APSRDEGs were interconnected, and nine hub genes were identified: CASP3, PTPRC, ELANE, HMOX1, CHUK, FLT1, JAK3, CTSL, and AURKA. GO and KEGG enrichment analyses indicated that these genes were significantly associated with key biological processes, cellular components, molecular functions, and pathways involved in AML. ROC curve analysis revealed that the expression levels of the nine hub genes differed significantly between the PAML and control groups. Immune infiltration analysis demonstrated a strong correlation between several hub genes and immune cells, with HMOX1 showing the strongest positive correlation with neutrophils.ConclusionThis study identified nine hub genes related to APS in pediatric AML. These findings suggest that APS may significantly affect immune infiltration and prognosis in pediatric AML, highlighting its potential as a therapeutic modulator for the disease.